IDENTIFYING THE POTENTIAL OF NEW CUSTOMERS FOR ISLAMIC BANKS FROM THE PERSPECTIVE OF CUSTOMER SWITCHING INTENTION - Suwarsi, Aqidah Asri; Putri Wulandari, Nanda (Universitas Airlangga, 2017)
This research aims to identify potential new customers Syariah banking regarding factors that cause the customer has customer switching intention. The research methodology used is a naturalistic approach to qualitative research. Researchers using primary data sources with the techniques of data collection via an in-depth interview. The subjects of this study are the conventional banking that has customer switching intention to Islamic banks. The method of the validity used is the using the extension of observation, whereas his credibility using triangular theory. The dwarf in the taking of the sample used was snowball sampling. Researchers using the method of analysis of Milles and Huberman, namely the reduction of data, data display, conclusion. Results found in this study is the potential of the new Islamic bank clients can be identified through the factors that cause the customer switching behavior intention is extrinsic factors include; sales promotion and brand quality and intrinsic factors include: variety seeking, consumer loyalty, the perception of consumers, consumer preferences, attitudes, knowledge of consumers, quality of service and religiosity.Keywords: Customer switching intention, Variety Seeking ,Consumer perception, Consumer knowledge , Religiousity